O sal da guerra: padre Antônio Vieira e as tópicas teológico-jurídicas na apreciação da guerra justa contra os índios - Freitas, Ludmila Gomides (2014)
The sixteenth and seventeenth-‐century Jesuit discourses translated and interpreted their encounters with the Native American otherness by theological, legal, political and rhetorical models from the Christian thought. The main subject of this thesis is the topic of war and, therefore, the theological-‐legal debate that had based this concept historically. The introduction of the Indians into the political and mystical body of Christian Portuguese monarchy and their use as work force for the economic exploitation of the land were two different political projects in those times. Although they were not mutually exclusive, they had permanently been in dispute, characterizing the conflictions between Jesuits, colonial authorities and settlers. The problem of the Just War became central in this context. ow the topic of war against the Indians compounded Antonio Vieira s providential and finalist understanding of history is a question that will be traced back from the reading of his sermons and letters. This aims to demonstrate that this Jesuit priest interpreted war in sacramental terms and so as an opportunity for men to collaborate with the divine plans. As a priest, Antonio Vieira sought to persuade the Portuguese settlers to set their will towards Christian actions. That was in compass with the Jesuit conception of salvation, which vindicated grace, faith and the role of free will as conditions for justification. In this sense, the justice of war and the enslavement of Indians were essential issues in the edification of a Portuguese Catholic Monarchy.